2022
DOI: 10.3389/fpls.2022.856646
|View full text |Cite
|
Sign up to set email alerts
|

Preharvest Hydrogen Peroxide Treatment Delays Leaf Senescence of Chinese Flowering Cabbage During Storage by Reducing Water Loss and Activating Antioxidant Defense System

Abstract: Leaf yellowing, an indicator of senescence, reduces commercial value of Chinese flowering cabbage after harvest. Hydrogen peroxide (H2O2) plays a dual role in mediating plant stress responses, but it is not clear whether and how it affects leaf senescence when exogenously stimulating the plants before harvest. Here, we found that preharvest application with low concentrations of H2O2 to root delays leaf senescence. Around 10 mM H2O2 reduced leaf yellowing rate by 8.2 and 26.4% relative to the control following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Leaves of Chinese flowering cabbage are prone to senescence after harvest, and senescence-associated gene 12 ( SAG12 ) is a critical gene promoting senescence progress [ 3 ]. The results here showed that BrSAG12 in the 6-BA treatment group was inhibited compared to that in the control ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Leaves of Chinese flowering cabbage are prone to senescence after harvest, and senescence-associated gene 12 ( SAG12 ) is a critical gene promoting senescence progress [ 3 ]. The results here showed that BrSAG12 in the 6-BA treatment group was inhibited compared to that in the control ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…The quality of Chinese flowering cabbage deteriorates rapidly after harvesting, which affects its commodity value and shelf life [ 3 ]. Green color and water retention of leaves are important commercial qualities of green leafy vegetables [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations